Comparison Between Linear and Non-Linear Fitting Methods in Adsorption Process - Yang, Fan; Song, Xiao-Jie; Wei, Wen-Mei; Yao, Shun; Xia, Chuan-Kai; Yang, Zi-Zhen (Asian Journal of Chemistry, 2014)
Active carbon was chosen as an adsorbent for adsorption of methylene blue and methyl orange. The effects of initial dye concentration and contact time on adsorption capacity of active carbon were investigated. The pseudo-first-order and pseudo-second-order kinetic models were applied to describe the kinetic data. The Freundlich and Langmuir adsorption models were used to describe adsorption mechanism. In the course of the data processing, linear and non-linear regression methods would be carried out for the best fitting of isotherm. Compared regression results, the character of linear and non-linear fitting methods were studied.